An XPS Study of the Oxidation of Reduced Ceria-Lanthana Nanocrystals - HOLMES, JUSTIN DEREK (Elsevier, 2011)
Detailed x-ray photoelectron spectroscopy (XPS) studies on the oxidation of an extensivley cleaned, reduced ceria-lanthana solid solution (12.5 mol% La to Ce) was performed. Uptake of oxygen during oxidation followed a logarithmic dependence on exposure. Differential charging during oxidation suggests that the oxidation process is diffusion limited. No evidence for surface 3+ cerium states in the fully oxidised samples, which are anion defect free within the limits of experimental accuracy, was found. The data suggest that there is no evidence for the inherent stability of anion vacancies (associated with Ce3+ sites) at the surface of these nanocrystals.
PUBLISHED
Keywords: Physical chemistry; nanocrystals